Impact of Artificial Intelligence and Virtual Reality on Educational Inclusion: A Systematic Review of Technologies Supporting Students with Disabilities - Angelos Chalkiadakis; Antonia Seremetaki; Athanasia Kanellou; Maria Kallishi; Anastasia Morfopoulou; Marina Moraitaki; Sofia Mastrokoukou (MDPI AG, 2024)
The emergence of Artificial Intelligence (AI) and Virtual Reality (VR) technologies offers transformative potential for the advancement of inclusive education, particularly for students with disabilities. This systematic review critically evaluates the current state of research to assess the impact of AI and VR on enhancing educational accessibility, personalisation and social inclusion in education. AI-driven adaptive systems can dynamically tailor learning experiences to individual needs, while VR offers immersive, multi-sensory environments that promote experiential learning. Despite these advances, the review also identifies significant challenges, including the high cost of implementation, technical barriers and limited teacher readiness, which hinder widespread adoption. Ethical concerns such as privacy and algorithmic bias are cited as key areas that need careful consideration. The findings underscore the urgent need for further empirical research to explore the long-term impact of these technologies and advocate for more equitable access to AI and VR tools in underserved educational settings. Ultimately, the review highlights the importance of integrating AI and VR as part of a broader strategy to foster genuinely inclusive learning environments that align with the goals of the Convention on the Rights of Persons with Disabilities (CRPD).